Knowledge regarding neonatal resuscitation among nurses in a municipality hospital: A cross-sectional study (Bangladesh Critical Care Journal, 2023)
Background: Neonatal resuscitation (NR) is a means to restore life of a baby from the state of asphyxia. It is a singlemost important intervention for neonates with birth asphyxia. Resuscitation in neonates is more challenging than thatof an adult or even an older infant or child. Poor resuscitation techniques can contribute to poor outcome in neonateswith birth asphyxia. Nurses being the front-liners to receive the newborn babies, level of knowledge about NR amongthem can affect the outcome in these patients.Objectives: This study was aimed to assess the level of knowledge regarding neonatal resuscitation among the nurses.Methodology: The study was conducted among the nurses of one of the municipality hospitals of Nepal by usingstructured self-administered questionnaires and total enumeration sampling method was used. A total of 56 responseswere obtained.Results: Among 56respondents, 51 (94.6%) were in the age group of 20-29 years. Majority of them 52 (92.8%) hadinadequate knowledge about neonatal resuscitation and only 4 (7.2%) had adequate knowledge.Conclusions: Majority of the nurses have inadequate knowledge regarding neonatal resuscitation. Training andeducational programs for nurses and on neonatal resuscitation can be helpfulBangladesh Crit Care J March 2023; 11 (1): 9-12